Students satisfaction using Bay Salam in purchasing attire through online shopping / Nur Elyana Rosli - Rosli, Nur Elyana (2019)
This study discuss about “student’s” satisfaction in purchasing attire through online shopping .There are many issues and problems arose regarding to the product and time delivery. These issues arise because online shopping is a necessity for people to buy goods easily. This study was focused on the concept bay Salam and the level student’s satisfaction in purchasing attire through online shopping in aspect “quality of product” and “time delivery” which are the objective of this study. These objective seen very relevance to meet criteria needed. Next, the method that has been used in this study is quantitative research method through questionnaire. The literature review section in this study purposely to give some information to the reader about contract bay Salam and student’s satisfaction in aspect quality of product and time delivery in purchasing attire through online shopping. The research will be shows after the literature review and will be explain in finding and analysis chapter. Chapter for finding and analysis are the main component in this study to discuss about the objective of this research. Lastly, discussion and recommendation are made in order to improve the quality of product and time delivery.